Aloe - Sauls, Aloysius Albeus (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis, 'Aloe', isse poetry collection, wat focus op modern Khoekhoegowab. Die opgittiekkinne wÄ“ke van my Ancestry se mÄ“nse van mÄ“nse,

xam-poets: Diä!kwain, Kweiten-ta-Ç ken,

a!kúnta,

HanÇ‚kass'o, en oek Ç Kabbo, deÄ“rie Dytse filoloog, Wilhelm Bleek, dien asse guide, moerrie vÄ“se gisoak in combinations van Ancient Indigenous, en modern Goema-klangke. Die purpose vannie collection is ommie use van Khoekhoegowab innie Afrikaans literature asse integral component te view, ennie iets foreign nie, diessèlle way wat Arabic, Indonesian, Malay en Dutch languages, die culture ennie language gishape en givorrim-it. DeÄ“l vannie skryf-style wat ek employ in my thesis isse fusion vannie lyric poetry van Linton Kwesi Johnson, Gill Scott Heron ennie praÄ t-poems van Peter Snyders, oa. Music, assie primal connection toerrie past, speÄ“lle central rÅ l in my wÄ“k asse 21st-century Indigenous writer. Die thesis reference die works van veteran cultural en linguistic aÄ tisse en lyrical poets; in echoes van marginalised en displaced creatives soes Tinariwen, wattie stÅ rie vannie Tuareg vocalise in woÅ dt en klang, ennie Chamorro poet, Craig Santos Perez van Guam, innie Western Pacific Ocean, wierrie indigenizing mandate se vlag lat wappe, bÃnne innie gisig vannie American presence daÄ .
Keywords: Creative writing (Higher education) -- South Africa; Nama language; Nama poetry 21st century; Lyric poetry 21st century; Diaries Authorship; Lyric poetry History and criticism; Fiction History and criticism